2008
DOI: 10.1677/joe-08-0424
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of dipeptidyl peptidase IV (DPP4) with the development of diabetes, dyslipidaemia and nephropathy: a streptozotocin-induced model using wild-type and DPP4-deficient rats

Abstract: We examined the role of dipeptidyl peptidase IV (DPP4) in the development of diabetes, dyslipidaemia and renal dysfunction induced by streptozotocin (STZ). F344/ DuCrlCrlj rats, which lack DPP4 activity, and wild-type rats were treated with STZ. Plasma DPP4 activity and biochemical parameters were measured until 42 days after STZ treatment. At the end of the experiment, renal function and DPP4 expressions of the kidney, liver, pancreas and adipose tissues were determined. Increases in blood glucose, cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 36 publications
7
69
0
1
Order By: Relevance
“…Additionally, using Otsuka Long-Evans Tokushima fatty rats, which display a spontaneously hyperphagic and obese phenotype in combination with hyperglycemia and hyperinsulinemia, we showed that plasma DPP4 activity changes in accordance with the progression of hyperinsulinemic obesity and pancreatic islet atrophy [7]. Furthermore, we reported that the plasma DPP4 level and DPP4 mRNA expression in some tissues increased progressively with the development of streptozotocin-induced type 1 diabetes [8].…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, using Otsuka Long-Evans Tokushima fatty rats, which display a spontaneously hyperphagic and obese phenotype in combination with hyperglycemia and hyperinsulinemia, we showed that plasma DPP4 activity changes in accordance with the progression of hyperinsulinemic obesity and pancreatic islet atrophy [7]. Furthermore, we reported that the plasma DPP4 level and DPP4 mRNA expression in some tissues increased progressively with the development of streptozotocin-induced type 1 diabetes [8].…”
mentioning
confidence: 75%
“…Although several clinical studies have investigated whether DPP4 activity is correlated with the onset or severity of diabetes and/or obesity, they have produced mixed results; i.e., plasma DPP4 activity levels were of 7-amino-4-methylcoumarin (AMC) from the synthetic substrate H-glycyl-prolyl-AMC (Gly-Pro-AMC; Sigma, St. Louis, MO, U.S.A.), as described previously [6][7][8]. Briefly, 5 μL of plasma were mixed with 35 μL of assay buffer (25 mmol/L HEPES, 140 mmol/L NaCl, 80 mmol/L MgCl 2 , and 1 % BSA; pH 7.8).…”
mentioning
confidence: 99%
“…DPP IV may be secreted from tubular epithelial cells following renal damage, which is known to cause the leakage of microvascular endothelial DPP IV in the kidney, or there may be some increased cleavage of the DPP IV pro-peptide. 7,[23][24][25] The morphological analysis of the AD-1 antibodyimmunoprecipitated urinary microvesicles by electron microscopy indicated that antibody binding during the isolation process did not perturb the morphology and structure of these vesicles. Based on the ratio of microvesicle-bound DPP IV to total urinary DPP IV, we propose that the microvesicle-bound type is the major form of DPP IV in urine.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important because such effects in the long term are probably not desirable and could accelerate diabetic nephropathy. Indeed, Kirino et al 12 report that in DPP-4 -deficient rats (F344/DuCrlCrlj rats; a strain of rats with a mutation in the DPP-4 gene that results in deficient DPP-4 activity), creatinine clearance 42 days after induction of diabetes (with streptozotocin) is 50% lower in DPP-4 -deficient versus wild-type rats.…”
mentioning
confidence: 99%